Therapeutic management of fibrosis in systemic sclerosis patients – an analysis from the Swiss EUSTAR cohort (Swiss Medical Weekly, 2024)
OBJECTIVES: Systemic sclerosis is a chronic autoimmune connective tissue disease leading to microvascular and fibrotic manifestations in multiple organs. Several treatment options and recommendations from different European countries are available. In this study, for which the ambit is Switzerland specifically, we aim to describe the treatment patterns of systemic sclerosis patients with fibrotic manifestations.METHODS: Systemic sclerosis patients were selected from six Swiss tertiary centres recorded in the multicentre, prospective European Scleroderma Trials and Research (EUSTAR) registry. Patients fulfilling the 2013 ACR/EULAR systemic sclerosis classification criteria at baseline were included. To determine the differences in treatment of varying degrees of fibrosis, four groups were identified: (1) patients with a modified Rodnan skin score (mRSS) >0; (2) those with mRSS ≥7; (3) those with interstitial lung disease (SSc-ILD), diagnosed by either chest X-Ray or high-resolution computed tomography; and (4) patients fulfilling one of the additional criteria for extensive interstitial lung disease, defined as interstitial lung disease involvement of >20% in high-resolution computed tomography, dyspnea NYHA-stage 3/4, or a predicted forced vital capacity (FVC) of 0, of whom 195 (33.1%) had mRSS ≥7; interstitial lung disease was diagnosed in 198 of 456 (43.4%), of whom 106 (18.0 %) showed extensive interstitial lung disease. Regarding non-biologic disease-modifying medications (DMARDs), the most frequently prescribed was methotrexate, followed by hydroxychloroquine and mycophenolate mofetil. Rituximab and tocilizumab were most frequently used among the biologic DMARDs. Specifically, 148/372 (39.8%) of treated patients with skin fibrosis received methotrexate, mycophenolate mofetil or rituximab, and 80/177 (45.2%) with interstitial lung disease received cyclophosphamide, mycophenolate mofetil, tocilizumab or rituximab. Most patients received a proton-pump inhibitor, and few patients underwent hematopoietic stem cell transplantation.CONCLUSION: Overall, in Switzerland, a wide range of medications is prescribed for systemic sclerosis patients. This includes modern, targeted treatments for which randomised controlled clinical trial have been recently reported.